Attraction of the sandfly Lutzomyia longipalpis to possible biomarker compounds from dogs infected with Leishmania infantum - Magalhães-Junior, J. T.; Oliva-Filho, A. De A.; Novais, H. O.; Mesquita, P. R.R.; M. Rodrigues, F.; Pinto, M. C. [UNESP]; Barrouin-Melo, S. M. (Wiley, 2019)
Lutzomyia longipalpis (Diptera: Psychodidae) is the primary vector of Leishmania infantum (Kinetoplastida: Trypanosomatidae) in the Americas. Studies have been carried out to identify new alternatives for monitoring and controlling this sandfly species, particularly with the use of chemical baits. The attractiveness of odours emitted by foxes and alcohols found in some plants has already been demonstrated in laboratory tests with Lu. longipalpis. However, no studies have evaluated the responses of these insects to volatile organic compounds (VOCs) emitted by dogs. The present study was carried out to investigate the effects on Lu. longipalpis of individual and blends of VOCs identified in hair from dogs infected with L. infantum. Effects in male and female Lu. longipalpis were assessed using wind tunnel methodology. Individual compounds including octanal, nonanal, decanal and heptadecane showed capacity for activating and/or attracting male Lu. longipalpis. Only decanal and nonanal showed effects on females. The combination of octanal, decanal and heptadecane increased activation and attraction behaviour in male sandflies, as did the blend of octanal and decanal. These findings indicate that VOCs emitted by dogs may be an interesting source of new attractants of sandflies.
Keywords: Kairomones; phlebotomines; wind tunnel